A Novel Way to Recruit Women Into the Applied Sciences - Nancy S. Bragg (Journal of Applied Communications, 1989)
To maintain a healthy agriculture program in a period of declining student enrollment, colleges must recruit actively. In response, the College of Life Sciences and Agriculture at University of Maine enhanced its recruitment program with a booklet aboul female role models. The focus was placed on women in the applied sciences. From responses to a 1988 questionnaire, 23 profiles were written and organized into the booklet aimed at junior and senior high school female students, their parents, and teachers. After extensive distribution, several staye groups "bought into" the project and used the publication in career programs and proiects. Recruitment results may take several years to be recorded, but, now these young students have more information on which to base their plans for the future.